Fold‐in Synthesis of a Pentabenzopentaaza[10]circulene. Issue 11 (20th January 2022) - Matsuo, Yusuke; Kise, Koki; Morimoto, Yuki; Osuka, Atsuhiro; Tanaka, Takayuki
Abstract: A pentabenzopentaaza[10]circulene has been synthesized as the largest fully conjugated hetero[ n ]circulene via a fold‐in oxidative fusion reaction of an ortho‐phenylene‐bridged cyclic pyrrole pentamer. This circulene takes a saddle‐distorted structure with bond lengths of the central ten‐membered‐ring in the range of 1.455–1.493 Å. Relatively broad absorption and fluorescence spectra were observed, which reflects its flexible structure, in accordance with the low‐temperature NMR spectra and theoretical calculations. The energy barrier for saddle‐to‐saddle interconversion was estimated to be quite small (≈3 kcal mol −1 ). Abstract : A pentabenzopentaaza[10]circulene has been synthesized as the largest fully conjugated hetero[ n ]circulene via a fold‐in oxidative fusion reaction of a cyclic pentapyrrole precursor. This circulene takes a saddle‐distorted structure with bond lengths of the central ten‐membered‐ring in the range of 1.455–1.493 Å. The energy barrier for saddle‐to‐saddle interconversion was estimated to be quite small (≈3 kcal mol −1 ).